2013
DOI: 10.1111/aor.12018
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐Assisted Thoracoscopic Hybrid Esophagectomy in the Semi‐Prone Position Under Pneumothorax

Abstract: We performed robot-assisted thoracoscopic hybrid esophagectomy using the da Vinci Surgical System and demonstrated the potential benefit of this minimally invasive lymphadenectomy. Between April 2010 and October 2011, four patients with intrathoracic esophageal cancer underwent hybrid esophagectomy in the semi-prone position using a 3-arm standard da Vinci and a conventional thoracoscopic maneuver. All thoracoscopic procedures were completed using a robot-assisted technique. Robot-assisted thoracoscopic esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The application of robotic technology is mainly focused on lymph node dissection along RLN because this is regarded a key step in curative resection for squamous cell carcinoma. As expected, Asian series reported a larger number of mediastinal lymph nodes with a higher rate of RLN palsy . Considering that interest in RATE is increasing in this region where VATS‐E with extensive ML is popular, more studies on RATE with extensive ML will undoubtedly be performed in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of robotic technology is mainly focused on lymph node dissection along RLN because this is regarded a key step in curative resection for squamous cell carcinoma. As expected, Asian series reported a larger number of mediastinal lymph nodes with a higher rate of RLN palsy . Considering that interest in RATE is increasing in this region where VATS‐E with extensive ML is popular, more studies on RATE with extensive ML will undoubtedly be performed in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…29 In comparison with Western series, RATE in the prone or semi-prone position followed by cervical esophagogastrostomy is preferred in Asian series. The application of robotic technology is mainly focused on lymph node dissection along RLN 8,10,31 because this is regarded a key step in curative resection for squamous cell carcinoma. As expected, Asian series reported a larger number of mediastinal lymph nodes with a higher rate of RLN palsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of publications that included robot‐assisted oesophagectomy are shown in Table . As for gastrectomy, early reports are case reports or small case series but more recent reports have larger numbers and results comparable to conventional surgery.…”
Section: Resultsmentioning
confidence: 99%
“…60) There are four articles related to three-stage RAE performed in the prone or semi-prone position (Table 4). 35,[60][61][62] In all four reports, no patients required conversion to either thoracoscopy or thoracotomy, and the rates of respiratory complications were quite low. In a study of the largest number of patients, Puntambekar, et al 61) reported a single institution experience of 32 RAE procedures in which mobilization of the esophagus was performed with the patient in the prone position.…”
Section: Robotically-assisted Esophageal Surgery In the Prone Positionmentioning
confidence: 89%